Magnetic resonance – guided treatment of low-flow vascular malformations and the technologies to potentiate adoption - Bailey, Christopher Ravi; Herrera, Daniel Giraldo; Neumeister, Nicolas; Weiss, Clifford Rabbe (Frontiers in Medicine, 2024)
Vascular malformations are congenital, non-neoplastic lesions that arise secondary to defects in angiogenesis. Vascular malformations are divided into high-flow (arteriovenous malformation) and low-flow (venous malformations and lymphatic malformations). Magnetic resonance imaging (MRI) is the standard for pre- and post-intervention assessments, while ultrasound (US), X-ray fluoroscopy and computed tomography (CT) are used for intra-procedural guidance. Sclerotherapy, an image-guided therapy that involves the injection of a sclerosant directly into the malformation, is typically the first-line therapy for treating low-flow vascular malformations. Sclerotherapy induces endothelial damage and necrosis/fibrosis with eventual involution of the malformation. Image-guided thermal therapies involve freezing or heating target tissue to induce cell death and necrosis. MRI is an alternative for intra-procedural guidance and monitoring during the treatment of vascular malformations. MR can provide dynamic, multiplanar imaging that delineates surrounding critical structures such as nerves and vasculature. Multiple studies have demonstrated that MR-guided treatment of vascular malformations is safe and effective. This review will detail 1) the use of MR for the classification and diagnosis of vascular malformations, 2) the current literature surrounding MR-guided treatment of vascular malformations, 3) a series of cases of MR-guided sclerotherapy and thermal ablation for the treatment of vascular malformations, and 4) a discussion of technologies that may potentiate interventional MRI adoption including high intensity focused ultrasound and guided laser ablation.